137k views
6 votes
TGive the values of a, b, and c from the standard form of the equation (2x + 1)(x - 2) = 0.

User MartinHN
by
4.6k points

1 Answer

5 votes

Answer:

a = 2

b = -3

c = -2

Explanation:

The standard form of a quadratic equation:

ax² + bx + c = 0

…………………………

in order to determine the equation

in standard form ,we have to expand the given expression :

(2x + 1)(x - 2) = 2x² - 4x + x - 2

= 2x² - (4x - x) - 2

= 2x² - 3x - 2

Then the standard form is :

2x² - 3x - 2

User Mike Robbins
by
5.0k points